The Influence of Individual, Organizational and Psychological Factors on the Employees’ Performance in Psychiatric Hospital Aceh - Aulia Wardi; Said Usman; Hajjul Kamil (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The aims of this study is to find out the influences of individual, organizational and psychological factors on employees. This research is a non-experimental study with a descriptive and analytic presentation that is to get a picture of the influence of individual factors, organizational factors, and psychological factors on the performance of Aceh Mental Hospital employees. The result shows that The performance of employees in Aceh Mental Hospital is in the bad category (60.2%). Individual characteristics that are not significant / not statistically related to the performance of Aceh Mental Hospital employees are age, education level. And years of service. The significant organizational characteristics statistically related to the performance of Aceh Mental Hospital employees are incentives, supervision, and work facilities. The significant psychological characteristic related statistically to the performance of Aceh Mental Hospital employees is motivation. While that which is not significantly related to employee performance is perception. The result of multivariate logistic regression analysis, Motivation variable is the variable that is statistically the most significantly related to the performance of Aceh Mental Hospital employees.